The Relationship between the Duration of Type 2 Diabetes Mellitus and Diabetic Neuropathy Complications - Anggraeni, Mia Anggi; Alfin, Riandi; Zikran; Syabariyah, Sitti (The Indonesian Institute of Science and Technology Research, 2024)
Diabetic neuropathy is one of the complications that often appear in patients with type 2 diabetes mellitus. This study was conducted to determine the relationship between the length of time suffering from type 2 diabetes mellitus with diabetic neuropathy complications. This study used a quantitative research design with correlative methods and a cross-sectional approach. The sampling technique used a consecutive sampling approach within 1 month to 86 patients with type 2 diabetes mellitus at Ujungberung Indah Health Center from April to May 2023. The inclusion criteria were patients with hyperglycemia. Instruments used to measure the length of time were medical records and diabetic neuropathy screening by the Ipswich touch test. Univariate analysis used descriptive and bivariate analysis using Kendall's tau. The results showed that most patients with type 2 diabetes mellitus who suffered from diabetic neuropathy on average suffered from diabetes mellitus (DM) for more than 5 years (45.3%). Statistical analysis of Kendall's tau with p-value= 0.000 (<0.05)., namely there was a significant relationship between the length of time suffering from type 2 diabetes mellitus with diabetic neuropathy. It can be concluded that there was a relationship between the length of time suffering from type 2 diabetes mellitus with diabetic neuropathy complications.